A new leafhopper genus of subtribe Paraboloponina (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini), with description of two new species from Papua New Guinea - Lu, Lin; Webb, M.d.; Zhang, Yalin (Zootaxa, 2018)
A new leafhopper genus Papuakutara gen. nov. is described from Papua New Guinea, with two new species, P. ficus sp. nov. and P. robustipenis sp. nov. Kutara lucidicosta (Walker, 1870) is transferred to Papuakutara comb. nov. A checklist of the genera in the subtribe Paraboloponina from Papua New Guinea and West Papua and a key for their separation are provided.